Strategy Formulation Of PT. Ajisaka Destar Utama - Hardi, Krisna Uvala; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
PT Ajisaka Destar Utama (PT. ADU) is one of Indonesian leading company in survey mapping industry. Further, the entrance of newcomers and the possibility of politic and economic instability will be a challenge for the company in the future. PT. ADU needs to have a strategy that will help the company reach its vision. The formulation of strategy started from external and internal environment using PESTEL and Porter’s Five Forces Analysis, Value Chain Analysis and Resource Based View Analysis. The information from external and internal environment analysis then used to generate strategy alternatives. The company needs to a vision, mission and values in order to align the strategy to their vision, mission and values. After stating their vision, mission and values, the company can choose the strategy starting from corporate level strategy until functional level strategy. In conclusion, PT. ADU currently has competitive advantage in the industry, but the company needs to prepare for the future challenge. Through analysis of the company’s environment, there is several strategy alternatives can be chosen by the company to achieve their dream in the future. Keywords: Survey Mapping, Strategy Formulation, Vision, Mission, Values, Corporate Strategy, Business Strategy, Functional Strategy